A Sharp Lieb-Thirring Inequality for Functional Difference Operators - Laptev, Ari; Schimmer, Lukas (Symmetry, Integrability and Geometry: Methods and Applications, 2021)
We prove sharp Lieb-Thirring type inequalities for the eigenvalues of a class of one-dimensional functional difference operators associated with mirror curves. We furthermore prove that the bottom of the essential spectrum of these operators is a resonance state.